The Formation of Old English Adverbs: Structural Description and Functional Explanation - Gema Maíz Villalta (Miscelánea: A Journal of English and American Studies, 2010)
The aim of this article is to analyze the formation of Old English adverbs (A-Y) as retrieved from the lexical database of Old English Nerthus within the theoretical framework of the Layered Structure of the Word. Firstly, a critical review of the literature on Old English adverb formation is offered in order to emphasize the necessity of an exhaustive and theoretically up-to-date study that distinguishes clearly synchronic from diachronic aspects on the one hand, and inflectional from derivational aspects on the other. Secondly, an exhaustive analysis of the derivation of adverbs in Old English by means of different word-formation processes (zero derivation, conversion, affixation and compounding) is given. In the theoretical part, the conclusion reached is that conversion requires a Complex Word structure and that a distinction has to be drawn between syntactic exocentricity and morphological exocentricity.
Keywords: Old English; word formation; adverb; Layered Structure of the Word; exocentricity